Leptomeningeal disease from melanoma—Poor prognosis despite new therapeutic modalities. (May 2021) - Chorti, Eleftheria; Kebir, Sied; Ahmed, Misbah S.; Keyvani, Kathy; Umutlu, Lale; Kanaki, Theodora; Zaremba, Anne; Reinboldt-Jockenhoefer, Finja; Knispel, Sarah; Gratsias, Emmanouil; Roesch, Alexander; Ugurel, Selma; et al.
Abstract: Objective: The development of leptomeningeal disease (LMD) among melanoma patients is associated with short survival. Unspecific clinical symptoms and imprecise diagnostic criteria often delay diagnosis. Because melanoma patients with LMD have been excluded from most clinical trials, the efficacy of immune checkpoint blockade (ICB) and targeted therapies (TTs) has not been adequately investigated among these patients. Methods: We performed a retrospective study in two tertiary-referral skin cancer centres to evaluate the clinical characteristics, diagnostics, treatments, and overall survival (OS) of melanoma patients with LMD between June 2011 and March 2019. Results: In total, 52 patients were included. The median age at LMD diagnosis was 58 years. Most patients (n = 30, 58%) were men. The median time from the first diagnosis of unresectable disease to the first diagnosis of LMD was 8.5 months (range 0–91.5 months). Most patients (65%, n = 34) were BRAF V600 mutated. Sixteen patients (31%) presented with LMD only, whereas 36 patients (69%) presented with concomitant brain metastases at LMD diagnosis. Eleven patients (21%) showed no evidence of extracranial disease. Forty-four patients (85%) had clinical symptoms at LMD diagnosis. Forty-two patients (81%) had received at least one prior therapy. Forty patients (77%) received at least one treatment after LMD diagnosis, including TT (n = 17), ICB (n = 13), bevacizumab (n = 1), radiotherapy (n = 3), and intrathecal chemotherapy (n = 1); five patients received both TT and ICB. Twelve patients (23%) received no treatment because of rapid progression of LMD. The median OS for the entire cohort was 2.9 months (95% confidence interval [CI] 1.7–4.1). Among patients receiving systemic therapy, OS was 3.7 months (95% CI 2.4–4.9). Conclusions: Systemic treatment with TT or ICB seems to improve OS among patients with LMD. However, despite new therapy modalities, the prognosis of LMD remains poor. Graphical abstract: Image 1 Highlights: Around 20% of the patients with leptomeningeal disease (LMD) received no treatment. The presence of a BRAF mutation seems to be higher in patients with LMD. At diagnosis of LMD, most of the patients had concomitant brain metastases. The prognosis of LMD remains poor with a median overall survival of 2.9 months.